Optimal. Leaf size=23 \[ 3 e^{-x-\frac {4+x}{x^3}} x \log (2+2 x) \]
________________________________________________________________________________________
Rubi [B] time = 1.75, antiderivative size = 51, normalized size of antiderivative = 2.22, number of steps used = 9, number of rules used = 5, integrand size = 56, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.089, Rules used = {1593, 6741, 6742, 2288, 2554} \begin {gather*} -\frac {3 e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} \left (-x^4+2 x+12\right ) \log (2 x+2)}{\left (-\frac {12}{x^4}-\frac {2}{x^3}+1\right ) x^3} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 1593
Rule 2288
Rule 2554
Rule 6741
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^{-\frac {4+x+x^4}{x^3}} \left (3 x^4+\left (36+42 x+6 x^2+3 x^3-3 x^5\right ) \log (2+2 x)\right )}{x^3 (1+x)} \, dx\\ &=\int \frac {e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} \left (3 x^4+\left (36+42 x+6 x^2+3 x^3-3 x^5\right ) \log (2+2 x)\right )}{x^3 (1+x)} \, dx\\ &=\int \left (\frac {3 e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} x}{1+x}+\frac {3 e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} \left (12+2 x+x^3-x^4\right ) \log (2+2 x)}{x^3}\right ) \, dx\\ &=3 \int \frac {e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} x}{1+x} \, dx+3 \int \frac {e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} \left (12+2 x+x^3-x^4\right ) \log (2+2 x)}{x^3} \, dx\\ &=-\frac {3 e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} \left (12+2 x-x^4\right ) \log (2+2 x)}{\left (1-\frac {12}{x^4}-\frac {2}{x^3}\right ) x^3}+3 \int \left (e^{-\frac {4}{x^3}-\frac {1}{x^2}-x}+\frac {e^{-\frac {4}{x^3}-\frac {1}{x^2}-x}}{-1-x}\right ) \, dx-3 \int \frac {e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} x}{1+x} \, dx\\ &=-\frac {3 e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} \left (12+2 x-x^4\right ) \log (2+2 x)}{\left (1-\frac {12}{x^4}-\frac {2}{x^3}\right ) x^3}+3 \int e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} \, dx-3 \int \left (e^{-\frac {4}{x^3}-\frac {1}{x^2}-x}+\frac {e^{-\frac {4}{x^3}-\frac {1}{x^2}-x}}{-1-x}\right ) \, dx+3 \int \frac {e^{-\frac {4}{x^3}-\frac {1}{x^2}-x}}{-1-x} \, dx\\ &=-\frac {3 e^{-\frac {4}{x^3}-\frac {1}{x^2}-x} \left (12+2 x-x^4\right ) \log (2+2 x)}{\left (1-\frac {12}{x^4}-\frac {2}{x^3}\right ) x^3}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.27, size = 22, normalized size = 0.96 \begin {gather*} 3 e^{-\frac {4+x+x^4}{x^3}} x \log (2 (1+x)) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.57, size = 21, normalized size = 0.91 \begin {gather*} 3 \, x e^{\left (-\frac {x^{4} + x + 4}{x^{3}}\right )} \log \left (2 \, x + 2\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.24, size = 21, normalized size = 0.91 \begin {gather*} 3 \, x e^{\left (-\frac {x^{4} + x + 4}{x^{3}}\right )} \log \left (2 \, x + 2\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.05, size = 22, normalized size = 0.96
method | result | size |
risch | \(3 x \,{\mathrm e}^{-\frac {x^{4}+x +4}{x^{3}}} \ln \left (2 x +2\right )\) | \(22\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.53, size = 28, normalized size = 1.22 \begin {gather*} 3 \, {\left (x \log \relax (2) + x \log \left (x + 1\right )\right )} e^{\left (-x - \frac {1}{x^{2}} - \frac {4}{x^{3}}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [F] time = 0.00, size = -1, normalized size = -0.04 \begin {gather*} \int \frac {{\mathrm {e}}^{-\frac {x^4+x+4}{x^3}}\,\left (3\,x^4+\ln \left (2\,x+2\right )\,\left (-3\,x^5+3\,x^3+6\,x^2+42\,x+36\right )\right )}{x^4+x^3} \,d x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.48, size = 20, normalized size = 0.87 \begin {gather*} 3 x e^{- \frac {x^{4} + x + 4}{x^{3}}} \log {\left (2 x + 2 \right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________